Mitochondria: Regulators of Cell Death and Survival - David J. Granville; Roberta A. Gottlieb (The Scientific World Journal, 2002)
The past 5 years has seen an intense surge in research devoted toward understanding the critical role of mitochondria in the regulation of cell death. Apoptosis can be initiated by a wide array of stimuli, inducing multiple signaling pathways that, for the most part, converge at the mitochondrion. Although classically considered the powerhouses of the cell, it is now understood that mitochondria are also “gatekeepers” that ultimately determine the fate of the cell. The mitochondrial decision as to whether a cell lives or dies is complex, involving protein-protein interactions, ionic changes, reactive oxygen species, and other mechanisms that require further elucidation. Once the death process is initiated, mitochondria undergo conformational changes, resulting in the release of cytochrome c (cyt c), caspases, endonucleases, and other factors leading to the onset and execution of apoptosis. The present review attempts to outline the complex milieu of events regulating the mitochondrial commitment to and processes involved in the implementation of the executioner phase of apoptotic cell death.